Postoperative imaging of the aorta - Li, Weier; Rongthong, Sasiprapa; Prabhakar, Anand M.; Hedgire, Sandeep (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
Considerable progress has been made in the management of diseases of the thoracic and abdominal aorta over the past decades, ranging from advances in open repair to the advent of minimally invasive endovascular techniques. Along with this comes an equivalent rise in imaging necessity for these patients, both in preoperative planning and postoperative surveillance. With the growing complexity and diversity of vascular procedures and techniques, it is essential to have a solid understanding of the imaging features and postoperative complications of these procedures to avoid imaging pitfalls. This review is an attempt to de ne the normal postoperative appearance and important complications of various open and endovascular surgical techniques of the thoracic and abdominal aorta.